The Village Head’s Leadership Style and Its Impact on the Effectiveness of Community Empowerment Programs through Community Participation - Sri Maryani; Nurul Hayat; Shoalihin Shoalihin (Advances in Management & Financial Reporting, 2026)
Purpose: This study aims to examine the effect of the village head's leadership style on the effectiveness of community empowerment programs, including the mediating role of community participation. Research Method: Using a quantitative correlational design, data were collected via Likert-scale questionnaires from 91 purposively sampled respondents from a population of 1,063 in Rababaka Village. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 3.0. Results and Discussion: The findings reveal that leadership style has a positive and significant effect on both program effectiveness and community participation. Moreover, community participation significantly influences program effectiveness and effectively mediates the relationship between leadership style and program effectiveness. Implications: These findings suggest that village governments should abandon top-down approaches in favor of empathetic and inclusive leadership to foster active citizen involvement. Future research should expand the geographical scope and employ mixed-methods approaches. Originality: This study uniquely identifies community participation not merely as an administrative requirement but as a crucial mediating mechanism that bridges leadership vision and program success within the specific socio-cultural dynamics of Rababaka Village.